Role of Cross-Cleft Contacts in NMDA Receptor Gating - Paganelli, Meaghan A. (Public Library of Science, 2013)
In response to brief glutamate exposure, NMDA receptors produce excitatory currents that have sub-maximal amplitudes and characteristically slow kinetics. The activation sequence starts when glutamate binds to residues located on the upper lobe of extracellularly located ligand-binding domains (LBDs) and then contacts lower lobe residues to bridge the cleft between the two hinged lobes. This event stabilizes a narrow-cleft LBD conformation and may facilitate subsequent inter-lobe contacts that further stabilize the closed cleft. Agonist efficacy has been traced to the degree of agonist-induced cleft-closure and may also depend on the stability of the closed-cleft conformation. To investigate how cross-cleft contacts contribute to the amplitude and kinetics of NMDA receptor response, we examined the activation reaction of GluN1/GluN2A receptors that had single-residue substitutions at the interface between LBD lobes. We found that side-chain truncations at residues of putative contact between lobes increased glutamate efficacy through independent additive mechanisms in GluN1 and GluN2A subunits. In contrast, removing side-chain charge with isosteric substitutions at the same sites decreased glutamate efficacy. These results support the view that in GluN1/GluN2A receptors’ natural interactions between residues on opposing sides of the ligand-binding cleft encode the stability of the glutamate-bound closed-cleft conformations and limit the degree of cleft closure, thus contributing to the sub-maximal response and emblematically slow NMDA receptor deactivation after brief stimulation.